Nuclear ionised outflows in a sample of 30 local galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Ruschel-Dutra, D.; Storchi-Bergmann, T.; Schnorr-Müller, A.
Abstract: Understanding active galactic nuclei (AGN) feedback is essential for building a coherent picture of the evolution of the super massive black hole and its host galaxy. To that end we have analysed the inner kiloparsec of a sample of 30 local AGN with spatially resolved optical spectroscopy. In this talk I will review the analysis of the ionised gas for the galaxies in our sample, including kinematical maps, emission line ratios and fluxes. The W 80 kinematical index is used to trace outflows, and also to provide an estimate for the outflowing velocity. Electron densities, derived from the [S II] ΛΛ6716, 6731Å lines, along with Hα luminosities and the sizes of the outflowing regions are employed in estimates of the outflowing gas mass. We find a median mass outflow rate of Ṁ = 0.3 M⊙ yr -1 and median outflow power of log [ P /(erg s -1 )] = 40.4.